The guide dog mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (New York : Scholastic, 1996)
When they help out at a guide dog training school, the Alden children meet several people who seem obsessed with a particular dog named Ginger.
RL3, 007-012.
610
Keywords: Mystery and detective stories; Guide dogs -- Fiction; Dogs -- Training -- Fiction; Brothers and sisters -- Fiction